Why are so many disabled individuals not working in Spain? A job search approach - José I. Silva; Judit Vall-Castello (Institute for the Study of Labor (IZA), 2012)
Unlike other disability systems in developed economies, the Spanish system allows partially disabled individuals to work while receiving disability benefits. The puzzle is, however, that employment rates in this group of individuals are very low. The aim of this paper is to understand the incentives and disincentives to work provided by the partial disability scheme in Spain. We first present a theoretical job search model for partially disabled individuals and then estimate a complementary log-log duration model. According to both models, the probability of finding a job falls with the level of disability, the age at which the individual starts receiving disability benefits, and the increase in the local unemployment rate. Moreover, as a result of an increase in the level of disability benefits we find a strong substitution effect that reduces the probability of disabled individuals older than 55 years finding a job to almost zero, in both of the two models. We simulate that the strong substitution effect would be replaced by an equally large income effect even if the increase in the benefits would not be suspended if the individual finds a job.
urn:nbn:de:101:1-2012042310047
Keywords: C41; I18; J64; 330; disability benefits; job search model; duration analysis; Behinderte; Arbeitsuche; Statistische Bestandsanalyse; Spanien